Rice Production Forecasting and Analysis of The Effect of Price on Rice Production In Karawang Regency - Zhillan Zhaliilaa; Slamet Abadi; Siti Mariyani (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Objective: This study aims to determine the best forecasting model for annual rice production in Karawang Regency for the next five years, and to analyze the effect of harvested dry grain prices and rice prices on rice production. Methodology: quantitative method with a time series approach, secondary data from BPS were analyzed using Double Exponential Smoothing Holts, Double Exponential Smoothing Brown, and ARIMA. The Mean Squared Deviation (MSD) criterion was used to select the best forecasting model. The analysis of price effects was carried out using multiple linear regression. Results: The results showed that the Double Exponential Smoothing Brown method was the best forecasting model with the lowest MSD (186,055,731). The forecast showed an increase in annual rice production in Karawang Regency by 1.59% in the next five years, indicating a positive trend. Regression analysis indicated that the price of harvested dry grain had a negative effect (-176.041) on rice production, while the price of rice had a positive effect (19.504). Novelty: Offers a rice production forecasting model by comparing three time series methods and integrating them with the analysis of the influence of paddy and rice prices. Originality: This study provides guidance for policy makers in designing local food security. Conclusion: Forecasting rice production in the next 5 years shows a significant increase and influence of rice and paddy prices on rice production. Type of Research: Quantitative research.